EVALUASI TANAH PENUTUP PERTAMBANGAN BATUBARA CV. INTAN KARYA MANDIRI, DI KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Jauhari, Rijal; Mahyudin, Idiannor; Lilimantik, Emmy; Hafizianor, Hafizianor (Universitas Lambung Mangkurat, 2023)
Coal mining activities using the open pit mining method can affect depreciation of the quality of the surrounding environment, one of which has an impact on reducing the classification criteria for soil chemical properties. The soil organic matter shrinks after being mined due to the lifting of the top layer due to the dismantling of the coal covering material. The research objective is to analyze the effect of mining activities on soil classification in the disposal area. The research method is descriptive analysis. Sampling and observation in Cintapuri Village, Cintapuri Darussalam District, Banjar Regency. Soil classification in Disposal 1, soil pH is classified as